A STUDY ON THE ANALYSIS OF CRITICAL FACTORS OF TECHNOLOGY TRANSFER EFFECTIVENESS IN THE AUTOMOTIVE SUPPLY CHAIN FOR INDONESIAN SMES - Kurnianingsih, Listiani
Automotive industries enhances and streamlines the supply chain system as the main strategy to increase its competitiveness. Technology is another aspect that defines the future of the auto industry. However, SMEs have a market reach that is too small to have their own research and development center. Thus SMEs are beginning to use technology transfer as a strategic means of meeting the challenges of business globalization. This study attempted to identify the critical factors of technology transfer effectiveness in the automotive supply chain for Indonesian SMEs and prioritize them. Five criteria and twenty-seven sub-criteria have been selected based on the literature review. For data collection, we gathered the expert’s opinions by questionnaire survey and processed them using Analytical Hierarchy Process (AHP) method. A pairwise comparison has been conducted to calculate the weight of criteria and sub-criteria and make a ranking for each sub-criteria under each criterion and then we evaluate the priority based on the overall weight of each critical factors sub-criteria. The result shows that Demand Environment has been found as the most important critical factors criteria, and culture has been rated as the most important critical factors sub-criteria. This study also provide the suggestion of policy implications for government and managerial implications for automotive companies and industries.